2021
DOI: 10.7554/elife.62183
|View full text |Cite
|
Sign up to set email alerts
|

Glycinergic axonal inhibition subserves acute spatial sensitivity to sudden increases in sound intensity

Abstract: Locomotion generates adventitious sounds which enable detection and localization of predators and prey. Such sounds contain brisk changes or transients in amplitude. We investigated the hypothesis that ill-understood temporal specializations in binaural circuits subserve lateralization of such sound transients, based on different time of arrival at the ears (interaural time differences, ITDs). We find that Lateral Superior Olive (LSO) neurons show exquisite ITD-sensitivity, reflecting extreme precision and rel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 79 publications
(164 reference statements)
1
18
0
Order By: Relevance
“…The most recent in vivo reports utilized whole-cell technique in gerbils and also found onset and multi-spiking LSO neurons 7 , 8 . These authors found that multi-spiking cells were near the margins of the nucleus, and they tended to have lower somatic synapse coverage suggesting they were not PNs but the marginal cells described by Helfert et al 62 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most recent in vivo reports utilized whole-cell technique in gerbils and also found onset and multi-spiking LSO neurons 7 , 8 . These authors found that multi-spiking cells were near the margins of the nucleus, and they tended to have lower somatic synapse coverage suggesting they were not PNs but the marginal cells described by Helfert et al 62 .…”
Section: Discussionmentioning
confidence: 99%
“…The onset cells tended to have greater somatic synapse coverage and were proposed to be the PNs designated by Helfert which made up 79% of LSO neurons. Franken et al also found that the LSO neurons with onset firing responses had short spike amplitudes normally associated with time-coding-specialized medial superior olive (MSO) neurons 63 and excelled at encoding of transients 8 . Thus, the authors proposed that a large majority of LSO neurons are time-coding-specialized, and the dominant function of LSO lies with ITD coding.…”
Section: Discussionmentioning
confidence: 99%
“…, 2015 ; Chen et al , 2019 ). A recent study reported evidence for an inhibitory “veto” mechanism at the axon initial segment of LSO principal neurons, with very narrow tuning to inter-aural time differences ( Franken et al. , 2021 ).…”
Section: Appendix: Deeper Issuesmentioning
confidence: 99%
“…A recent study reported evidence for an inhibitory “veto” mechanism at the axon initial segment of LSO principal neurons, with very narrow tuning to inter-aural time differences ( Franken et al. , 2021 ). Transmission failure at reputed “secure” synapses in CN and MNTB might conceivably reflect a similar veto mechanism ( Mc Laughlin et al , 2008 ; Englitz et al , 2009 ; Stasiak et al , 2018 ).…”
Section: Appendix: Deeper Issuesmentioning
confidence: 99%
“…Interestingly, the AIS of each BC is contacted by multiple small inputs. Inhibitory inputs onto the AIS of other neuron types have been shown experimentally and computationally to modulate spike generation ( Bae et al, 2021 ; Schneider-Mizell et al, 2021 ; Veres et al, 2014 ; Franken et al, 2021 ). We reveal that in nearly all BCs one of the large somatic inputs extends onto the hillock and AIS.…”
Section: Discussionmentioning
confidence: 99%